2012
DOI: 10.1002/gcc.21965
|View full text |Cite
|
Sign up to set email alerts
|

Clinically significant copy number alterations and complex rearrangements of MYB and NFIB in head and neck adenoid cystic carcinoma

Abstract: Adenoid cystic carcinoma (ACC) of the head and neck is a malignant tumor with poor long-term prognosis. Besides the recently identified MYB-NFIB fusion oncogene generated by a t(6;9) translocation, little is known about other genetic alterations in ACC. Using high-resolution, array-based comparative genomic hybridization, and massively paired-end sequencing, we explored genomic alterations in 40 frozen ACCs. Eighty-six percent of the tumors expressed MYB-NFIB fusion transcripts and 97% overexpressed MYB mRNA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
124
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 143 publications
(138 citation statements)
references
References 48 publications
10
124
0
1
Order By: Relevance
“…However, finding a compound that specifically inhibits the MYB transcriptional function presents a formidable challenge. On the other hand, some of the proposed downstream effectors of MYB may be more “druggable.” These include cell proliferation proteins ( MYC , CD53 , FGF2 , VEGFA , and KIT ), cell cycle proteins ( CCNB1 , CDC2 , and MAD1L1 ), apoptosis‐related markers ( API5 , BCL2 , BIRC3 , HSPA8 , and SET ), and cellular adhesion molecules ( CD34 ) 28. In addition, the tumor DNA studies suggest that agents that inhibit signaling through the Notch, protein kinase A, or FGF‐insulin‐like growth factor‐PI3K pathways or block the epigenetic effects of chromatin remodeling may also be active in ACC 24, 25…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, finding a compound that specifically inhibits the MYB transcriptional function presents a formidable challenge. On the other hand, some of the proposed downstream effectors of MYB may be more “druggable.” These include cell proliferation proteins ( MYC , CD53 , FGF2 , VEGFA , and KIT ), cell cycle proteins ( CCNB1 , CDC2 , and MAD1L1 ), apoptosis‐related markers ( API5 , BCL2 , BIRC3 , HSPA8 , and SET ), and cellular adhesion molecules ( CD34 ) 28. In addition, the tumor DNA studies suggest that agents that inhibit signaling through the Notch, protein kinase A, or FGF‐insulin‐like growth factor‐PI3K pathways or block the epigenetic effects of chromatin remodeling may also be active in ACC 24, 25…”
Section: Discussionmentioning
confidence: 99%
“…However, the most intriguing alteration is a translocation between chromosomes 6q and 9p [(6;9)(q22–23;p23–24)]. Persson et al27, 28 were the first to report that this rearrangement juxtaposes the genes for the MYB and nuclear factor I/B (NFIB) transcription factors. This translocation seems to be specific for ACC, found in up to 86% of these tumors,24, 27, 28 and may be helpful in differentiating these tumors from other forms of carcinoma, such as pleomorphic adenoma 29, 30.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…89 In contrast, salivary gland adenoid cystic carcinomas have multiple recurrent copy number alterations some of which are associated with a poor prognosis. 90,91 Dedifferentiation and progression to high-grade lesions (no specific type grade 3, malignant myoepithelial, or of mixed epithelial-myoepithelial type) have been described both in salivary gland and breast tumors. 59,71,[92][93][94][95][96][97] It has been suggested that new genetic alterations gradually accumulate in subclones of these tumors leading to clonal evolution and disease progression.…”
Section: Discussionmentioning
confidence: 99%